In situlaser annealing as pathway for the metal free synthesis of tailored nanographenes - Milotti, Valeria; Melle-Franco, Manuel; Steiner, Ann-Kristin; Verbitskii, Ivan; Amsharov, Konstantin; Pichler, Thomas (Nanoscale Advances, 2021)
Tailored synthesis of nanographenes, and especially graphene nanoribbons (GNR), has been achieved on metal substratesviaa bottom-up approach from organic precursors, which paves the way to their application in nanoelectronics and optoelectronics. Since quantum confinement in nanographenes leads to the creation of peculiar band structures, strongly influenced by their topological characteristics, it is important to be able to exactly engineer them in order to precisely tune their electronic, optical and magnetic properties. However practical application of these materials requires post-synthesis transfer to insulating substrates. Recently, cyclodehydrofluorination of fluorinated organic precursors has been shown to be a promising pathway to achieve metal-free bottom-up synthesis of nanographenes. Here we present how to applyin situlaser annealing to induce cyclodehydrofluorination leading to nanographene formation directly on non-metallic surfaces. In this work, we analyze the changes in the Raman fingerprint of the fluorinated precursor tetrafluoro-diphenyl-quinquephenyl (TDQ) during the laser annealing process in high vacuum (HV), demonstrating that both heating and photo-induced processes influence the cyclization process. Hence,in situlaser annealing allows not only to influence chemical reactions, but also to have a fast and contact-free monitoring of the reaction products. Optimization of the laser annealing process adds a new level of control in the tailored synthesis of nanographenes on non-metallic substrates. This is a very promising pathway to unravel the full application potential of nanographenes in general and GNR in particular, enabling a fast optimization of precursor molecules and substrate geometry engineered for specific applications.
CRIS-Team Scopus Importer:2021-02-26